The Development of a GIS database for blackspot area in Federal Route 24 - Noor Azmi, Norhisham; Sarif, Abdul Sukor (Progress in Engineering Application and Technology, 2023)
Federal Route 24, commonly known as Jalan Muar–Yong Peng, is a federal highway in Johor, Malaysia. This road connects Muar (Bandar Maharani) in the west to Yong Peng in the east. The Yong Peng Interchange connects it to the North-South Expressway. This study looks into the identification of blackspot locations on Federal Route 024, as well as solutions for preventing or reducing the danger of such mishaps in the future. This research methodology was conducted to guide this research which aims to investigate the effectiveness of GIS software. In order to identify and mapping the blackspot area in Malaysia. This research needs to involve the police to gather all the information and data that we needed. All the data collected will be transferred into the GIS software to sort them and reveal the blackspot area. Then the area will be pinpointed while doing the mapping work based on the data collected. The implementation of the methodology was done by using the collected data from various sources by the blackspot accident data in FT024 Muar - Yong Peng. It will be followed by the process and geoprocessing technique for selecting the site location for the prone accident blackspot area. The conclusion after using the selected method which is using QGIS software to determine the blackspot area and creating a map with pinpointed area using the data collected. Since data collecting is practical and beneficial, recommendations will be given so that lectures and courses be made more easily accessible to all institutions of higher learning.